Variability of trace element distribution in Noccaea spp., Arabidopsis spp., and Thlaspi arvense leaves: the role of plant species and element accumulation ability - Galiová, Michaela Vašinová; Száková, Jiřina; Prokeš, Lubomír; Čadková, Zuzana; Coufalík, Pavel; Kanický, Viktor; Otruba, Vítězslav; Tlustoš, Pavel (Environmental monitoring and assessment, 2019)
Laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) was applied for the determination of Cd and Zn distributions within the leaves of Cd- and Zn-hyperaccumulating plants, Noccaea caerulescens, N. praecox, and Arabidopsis halleri, in contrast to nonaccumulator species, Thlaspi arvense and A. thaliana. The elemental mapping of the selected leaf area was accomplished via line scans with a 110-μm-diameter laser beam at a 37-μm s-1 scan speed and repetition rate of 10 Hz. The lines were spaced 180 μm apart and ablated at an energy density of 2 J cm-2. The elemental imaging clearly confirmed that Cd was predominantly distributed within the parenchyma of the T. arvense, whereas in the Noccaea spp. and A. halleri, the highest intensity Cd signal was observed in the veins of the leaves. For Zn, higher intensities were observed in the veins for all the plant species except for A. thaliana. Close relationships between Zn and Ca were identified for the Noccaea spp. leaves. These relationships were not confirmed for A. halleri. Significant correlations were also proved between the Cd and Zn distribution in A. halleri, but not for the Noccaea spp. For both T. arvense and A. thaliana, no relevant significant relationship for the interpretation of the results was observed. Thus, the LA-ICP-MS imaging is proved as a relevant technique for the description and understanding of the elements in hyperaccumulating or highly accumulating plant species, although its sensitivity for the natural element contents in nonaccumulator plant species is still insufficient.
Keywords: kadmium; stopové prvky; Laser ablation; listy rostlin; monitorování životního prostředí; Cadmium; Thlaspi; Trace Elements; Zinc; Trace elements; Plant Leaves; Hyperaccumulating plants; Elemental mapping; zinek; Brassicaceae; Plant Roots; Environmental Monitoring; Arabidopsis; kořeny rostlin